Valley of death: A proposal to build a "translational bridge" for the next generation. (February 2017) - Gamo, Nao J.; Birknow, Michelle R.; Sullivan, Danielle; Kondo, Mari A.; Horiuchi, Yasue; Sakurai, Takeshi; Slusher, Barbara S.; Sawa, Akira
Highlights: There is a dire need to invest in novel drug discovery for psychiatric disorders. "Valley of death" between academia and industry is exacerbated for brain disorders. We propose an academic infrastructure to teach drug discovery and development. We propose a framework for academic institutions to perform translational research. Abstract: There is a great need for novel drug discovery for major mental illnesses, but multiple levels of challenges exist in both academia and industry, spanning from scientific understanding and institutional infrastructure to business risk and feasibility. The "valley of death, " the large gap between basic scientific research and translation to novel therapeutics, underscores the need to restructure education and academic research to cultivate the fertile interface between academia and industry. In this opinion piece, we propose strategies to educate young trainees in the process of drug discovery and development, and prepare them for careers across this spectrum. In addition, we describe a research framework that considers the disease trajectory and underlying biology of mental disorders, which will help to address the core pathophysiology in novel treatments, and may even allow early detection and intervention. We hope that these changes will increase understanding among academia, industry, and government, which will ultimately improve the diagnosis, prognosis and treatment of mental disorders.